Pengaruh Motivasi dan Gaya Kepemimpinan Terhadap Kinerja Pegawai pada Bagian Protokol Pemerintah Kota Yogyakarta - Rini Falensia; Sekar Galuh Septyawati; Muhammad Alfin Putra Mulya; Sentot Imam Wahjono (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This research aims to: (1) analyze how motivation influences employee performance within the Protocol Division of Yogyakarta City Government, (2) examine the role of leadership style in affecting employee performance in the same context, and (3) assess the combined impact of motivation and leadership style on employee performance. The study surveyed all 40 employees working in the Protocol Division, applying a saturated sampling method where the entire population serves as the sample. The regression analysis yielded the equation Y = 0.244X1 + 0.671X2. The statistical analysis confirmed the validity and reliability of the research instruments. Classical assumption tests indicated that the regression model was free from multicollinearity, heteroscedasticity, and followed a normal distribution. Hypothesis testing showed a t-value of 2.072 and a significance level of 0.045, indicating that motivation has a statistically significant positive effect on performance. Additionally, the leadership variable recorded a t-value of 5.694 with a 0.000 significance level, further confirming a significant positive influence on performance. Leadership style emerged as the most influential factor, with a coefficient of 0.671. The findings conclude that both motivation and leadership style play significant roles in enhancing employee performance in the Yogyakarta City Government’s Protocol Division.